Tanbih Sufi Counseling Guidance Thoriqoh Qodiriyyah Naqshbandiyyah Suryalaya To Cultivate Moderate Religious Attitudes Among Students (Research At Sirnarasa Islamic Boarding School ) - Cahya Purnawati, Ai; Isep Zainal Arifin; Hajir Tajiri (Coution: Journal Counseling and Education, 2025)
Religious moderation counseling needs to be provided to Islamic boarding school students as future scholars and national leaders. Indonesia as a heterogeneous country needs a religious leader who is able to unite the nation. Islamic boarding schools are the most appropriate place for instilling tolerant, inclusive, and moderate Islamic values. Religious moderation in Sirnarasa Islamic boarding school provides Sufi counseling guidance based on Tanbih Thoriqoh Qodiriyyah Naqsyabandiyyah Suryalaya to foster a moderate attitude in religious students. The purpose of this study is to examine the process of Tanbih Thoriqoh Qodiriyyah Naqsyabandiyyah Counseling Guidance to foster a moderate attitude in religious students in Sirnarasa. The methodology of this study uses a qualitative approach using the case study method with observation, interview, and document techniques. The results of this study are: (1) Abah Aos as Mursyid Thoriqoh Qodiriyyah Naqsyabandiyyah becomes a counselor and role model for moderate attitudes in Sirnarasa students. (2) All students are given Tanbih Thoriqoh Qodiriyyah Naqsyabandiyyah Counseling Guidance to become moderate individuals and ready to live in a plural society. (3) Tanbih Thoriqoh Qodiriyyah Naqsyabandiyyah Counseling Guidance is based on Sufism teachings, especially Tanbih Thoriqoh Qodiriyyah Naqsyabandiyyah with methods and stages that are adapted to Islamic Boarding School activities such as reading the nine pillars of world civilization, manaqib and suhbah.